Carta del "Commanding General, Department of Porto Rico" a Rafael Nieto Abeillé - Todd, Roberto H.; Commanding General, Department of Porto Rico (My University, 1899)
Retención de la posición de Magistrado de la Corte Suprema
Keywords: Headquarters, Department of Porto Rico; Office of the Judge Advocate; Nieto Abeillé, Rafael; Ealo y Domínguez, Luis de